2013
DOI: 10.1177/0022034513501323
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Aggravates Iodoacetate-induced Temporomandibular Joint Osteoarthritis

Abstract: Temporomandibular joint osteoarthritis (TMJOA) is clinically characterized by female preponderance, with a female-to-male ratio of more than 2:1; however, the underlying mechanism remains obscure. We examined the effects of estrogen on TMJOA induced by monosodium iodoacetate. Female rats were randomly and equally divided into 5 groups: control, sham-ovariectomized, and ovariectomized rats treated, respectively, with 17β-estradiol (E2) at doses of 0 µg, 20 µg, and 80 µg/day until the end of the experiment. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 27 publications
4
32
0
1
Order By: Relevance
“…Interestingly, in terms of the severity for TMD, sharper symptoms of TMDs were exhibited in females than in males [25,26]. The exact reasons have not yet been determined; however, given the striking predominance of affected women, previous studies proposed that the results could be partially attributed to hormonal influence, and a rise in estrogen levels may be an important risk factor for the pathogenesis of TMD [25,[27][28][29]. It should be emphasized that TMDs are complex multifactorial disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in terms of the severity for TMD, sharper symptoms of TMDs were exhibited in females than in males [25,26]. The exact reasons have not yet been determined; however, given the striking predominance of affected women, previous studies proposed that the results could be partially attributed to hormonal influence, and a rise in estrogen levels may be an important risk factor for the pathogenesis of TMD [25,[27][28][29]. It should be emphasized that TMDs are complex multifactorial disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The female preponderance and occurrence in the circumpubertal phases of TMJ OA suggests the possible function of female sex hormones and GH in the disease process. The destructive effects of oestrogen on condylar cartilage and subchondral bone have been suggested and GH appears to be involved in chondrocyte proliferation and protection of the subchondral bone . Oestrogen and GH are also important in the pubertal growth spurt and fusion of the epiphyseal growth plate .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sex hormones and GH can influence the development of degenerative changes in joints. The destructive effect of oestrogen on the TMJ condylar cartilage and both erosive and protective effects of oestrogen on the TMJ subchondral bone have been well reported . GH deficiency induced damage of articular cartilage in the knee joint has also been demonstrated .…”
Section: Introductionmentioning
confidence: 96%
“…A pharmacologic dose of 17β‐estradiol has been shown to increase inflammation and alter TMJ tissue morphologies. Wang et al () found that high pharmacologic 17β‐estradiol aggravated iodoacetate‐induced TMJ osteoarthritis. A pharmacologic bolus dose of 20 or 80 μg/day yielded plasma 17β‐estradiol levels which were supraphysiologic.…”
Section: Physiologic and Pharmacologic Estrogenic Effects On Tmj Strumentioning
confidence: 99%
“…A pharmacologic bolus dose of 20 or 80 μg/day yielded plasma 17β‐estradiol levels which were supraphysiologic. This high concentration of estradiol potentiated cartilage degradation, subchondral bone erosion and complete chondrocyte loss with the most damage seen in the group receiving the 80 µg/day dose (Wang et al, ). This is consistent with early findings that suggest high pharmacologic estrogen causes a decrease in collagen and protein content in the TMJ disk (Abubaker, Hebda, & Gunsolley, ).…”
Section: Physiologic and Pharmacologic Estrogenic Effects On Tmj Strumentioning
confidence: 99%